Implications of cloud-computing services in records management in Africa: Achilles heels of the digital era? - Tshepho Mosweu; Lungile Luthuli; Olefhile Mosweu (South African Journal of Information Management, 2019)
Background: Cloud-based services are increasingly used by organisations around the world and Africa is no exception. Literature has revealed that organisations adopt them as they offer efficient and cost-effective services. Notably, Africa is generally at an infant stage in the adoption of cloud-computing services in records management.